Self-based goals, underlying reasons, performance and discrete emotions among parkrunners - Mulvenna, Mairi; Adie, James W.; Tramontano, Carlo (Frontiers in Psychology, 2023)
A temporal sequence of hypothesized relationships was tested between self-based goals and their underlying reasons → stress appraisals → performance and emotions, among UK parkrunners. A conditional process model was also examined to ascertain the potential moderating role of self-determined reasons in explaining the indirect relationship of self-based goals predicting performance and emotions via stress appraisals. Utilizing a prospective design, 324 parkrunners (Mage=45.27; SD=10.73 years) completed online measures of self-based goals, their underlying reasons at 7 days (T1), and stress appraisals at 24 hours (T2), prior to their next UK parkrun. Performance data and discrete emotions (pride and shame) were reported 24 hours post-parkrun (T3). Structural Equation Modeling revealed partial support for the hypothesized model. More specifically, findings suggested that: 1) T1 self-determined reasons underpinning a self-approach goal positively predicted T2 challenge appraisals and T3 pride, 2) T1 self-determined reasons for pursuing a self-avoidance goal corresponded to reduced T3 performance and shame, 3) T2 challenge and threat appraisals were found to positively relate to T3 pride, and 4) the slower parkrunners ran, the more shame they felt post-event. T2 challenge and threat appraisals were found to mediate the relationship between T1 self-determined reasons underlying a self-approach goal and T3 pride. Further analysis failed to support a conditional process model. Our findings suggest the intensity of pursuing a self-based goal does not matter at all, but underlying self-determined reasons are a key driver influencing stress appraisals, performance and subsequent emotions among parkrunners.